Palynomorphometry in ferns: Ctenitis (Dryopteridaceae), a case of study in the Southern Cone of America - Daniel Alejandro Gorrer (Rodriguésia, 2023)
Abstract The morphometric knowledge about the spores of the Ctenitis has not yet been deepened. Considering the folded spores of this genus which inhabit the Southern Cone of America the aims were to increase infrageneric knowledge, to evaluate the relationship among the morphometric characters of the folded spores in these Ctenitis species and to verify the spore’s morphometry as a taxonomic tool. This study was performed with herbarium material. The spores were analyzed with light microscopy (LM) and scanning electron microscopy (SEM). The variables analyzed were: major and minor equatorial diameter, polar diameter, length of the laesura and length, width and height of the folds. The test chosen to analyze the study variables was ANOVA. Four spore sets are proposed. The “elongate-type” is made up of C. aspidioides and C. nervata. The “medium-type” is made up of C. anniesii, C. distans, C. falciculata and C. paranaensis. The “handle shape-type” is represented by C. bigarellae, C. eriocaulis and C. submarginalis. Finally, the “short-type”, consists only of C. deflexa. The morphometric data of spores together with the statistical analysis provided useful information for the distinction of some Ctenitis species studied in the Southern Cone of America. These results contribute to the studies aeropalynologycal and palaeopalynological.